Medvrstniško nasilje kot skupinski pojav: predstavitev izhodišč in ciljev raziskave - Košir, Katja (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Peer violence is a complex phenomenon embedded in a social context, and therefore it needs to be studied using different approaches and incorporating different perspectives. This chapter presents the starting points and goals of the project, in which we used a variety of data sources (self-reporting, peer nominations, teacher reporting) and advanced research designs (longitudinal research, focus groups) to investigate the reciprocal relationship between psychosocial characteristics of students and classes and students' involvement in peer violence in early adolescence. We additionally examined the role of psychosocial characteristics of individuals and classes and involvement in peer violence in relation to students' school adjustment. The project included two studies: a core longitudinal study with three measurements, conducted on a large sample of adolescents, and a qualitative study. Based on the findings of both studies, we have developed guidelines for designing preventive and intervention activities to support such classroom contexts that represent a protective factor against peer violence in adolescence.